Disclosure of major objects of intellectual property, reflecting the geographical origin of goods - Yadreuski, Aleh (Journal of the Belarusian State University. Law, 2019)
The article deals with the legal protection of intellectual property objects, which reflect the geographical place of origin – the indication of source, geographical indications, appellation of origin. Based on the study of international acts and positions of scientists identified the author of various points of view on the nature of the legal protection of indications of source. As a result of comparing them for the first time highlighted criteria, different combinations of which stipulate the possibility of protection of designation as an indication of source, geographical indications, appellations of origin. Based on the study of national legislations of foreign countries the author classifies the main systems of legal protection of geographical designations. The analysis allows to build a system of legal protection of geographical designations by means of intellectual property objects.
Keywords: geographical origin; intellectual property; indication of origin; geographical indications; appellations of origin